To the issue of etymology of the suffix -ман/-мен in the kazakh language and its possible relations to german -man (-mann) (Eurasian Journal of Philology Science and Education, 2018)
This article deals with etymology of Kazakh word-building suffix -ман / -мен and its possible relativeness to Indo-European languages’ -man (-mann). The actuality of this theme is urged with appearance of numerous neologisms with this suffix in Kazakh denoting the activity of a man. The aim of this article is to hold etymological analysis of suffix -ман / -мен in the Kazakh language, -man in English and -mann in German and to define available etymological and semantic ties between these suffixes. Results of the conducted analyses have shown that the given word-building morphemes in different-structured languages such as Kazakh, English and German languages might be genetically related as historically they refer to one and the same language family.